Magazine production - Whittaker, Jason 1969- (Media skills, 2017)
Magazine Production is a guide to the practical processes of taking a magazine from initial idea to final print and digital editions, and is aimed at those who wish to produce a title as part of their studies or for distribution on a small scale. It gives readers an overview of the essential elements to take into consideration when creating a magazine, including legal issues, the relation between editorial and design, and preparation for print or digital distribution. Magazine Production will explain the business of magazines in the UK, Europe and North America, and the roles of marketing, publishing and advertising in establishing a successful title. With information on professional bodies such as the Periodical Publishers Association, this book will provide readers with a clear understanding of what is needed to succeed in a career in magazines. Magazine Production includes: an introduction to the history, markets and audiences of magazines explanations of the roles of publishers and advertising teams as part of the business of magazines how to publicise a title and attract interest via a media pack guidance on setting up editorial teams, and best practice for producing feature, news and review copy information on designing and laying out a title for print or digital distribution legal and ethical issues affecting magazine editors and publishers a consideration of the future of magazines.